Análises bromatológicas e fitoquímicas de frutos de Licania tomentosa (Benth) FRITSCH - Teixeira, Luciane de Lira (2012)
This study conducted chemical analyzes of the fruits of Licania tomentosa Benth belonging to the Chrysobalanaceae family, order and superorder Rosiflorae Rosales. Samples were collected in February 2011 in the city of Natal - RN. The fruits were separated into peel, pulp and seed, and the samples were analyzed on moisture and ash by thermogravimetric methods, reducing and total sugars, lipids by Soxhlet extraction, minerals by ICP / OES and other analyzes by physical measurements of the fruit. The fruits for the analysis of determination of flavonoids and phenolic compounds were dried at 40 ° C and ground. For the analyzes to determine the content of phenolics and flavonols was used spectroscopy in the visible region, and also performed the characterization of ethanol extracts by high performance liquid chromatography and test for antioxidant activity hydroethanolic extracts. The results obtained are about 83.9% of the fruits have a length between 4.0 to 6.0 cm with respect to the diameter of the fruit about 97.4% of the fruits have a diameter between 2.0 - 4, 0 cm, mean weight of 36.14 g (7.86), the bark showed 60.5 (1.5)% relative humidity, the flesh 72.3 (0.9) and 44.4 seeds (0.4 )%, the bark showed 0.22 (0.00)% ash, the pulp 1.41 (0.01)% and the seed 1.18 (0.01)%, the bark showed 3.73 (0, 09) mg lipids / 100 g sample of the pulp 0.40 (0.04) and the seed 0.05 (0.00). With respect to reducing sugars and total gave the results, 16.23 (0.23) g/100g and 20.70 (0.24) g/100g. The fruit is presented with a good source of nutrients especially carbohydrates and lipids. The analysis for determining the antioxidant activity tests were performed reducing power and antioxidant capacity, the antioxidant capacity of hydroethanolic extracts of peel and pulp showed similar results, with higher concentrations however hydroethanolic bark extract. Regarding the content of phenolics and flavonoids hidroetanílico bark extract showed higher concentration values. The characterization of the extracts by high performance liquid chromatography identified the following compounds by retention time indicated by the race of the standards: galic acid, kaempferol and kaempferol derivatives. Considering the results of the fruit Licania tomentosa Benth may be an alternative food by analysis of their nutritional content and has substances with antioxidant action